Average vs. local structure and composition-property phase diagram of K0.5Na0.5NbO3-Bi½Na½TiO3 system. Issue 4 (April 2017) - Liu, Laijun; Knapp, Michael; Ehrenberg, Helmut; Fang, Liang; Fan, Huiqing; Schmitt, Ljubomira Ana; Fuess, Hartmut; Hoelzel, Markus; Dammak, Hichem; Thi, Mai Pham; Hinterstein, Manuel
Abstract: Phase diagram of the solid solution system K0.5 Na0.5 NbO3 - Bi½ Na½ TiO3 [(1-x)KNN-xBNT] has been established from dielectric permittivity measurement and structure analyses. The unit cell volumes continuously decrease depending on the composition, while the local structure maintains distortions away from the cubic average structure in the range 0.10 ≤  x  ≤ 0.90. No clear correspondence for the temperatures of phase transition exists between structural studies and physical properties. The dielectric behavior is depicted successively from normal ferroelectric, diffuse phase transition, re-entrant-like relaxor, relaxor + dipolar glass-like relaxor, BNT-like relaxor with the increase of BNT. A comprehensive composition-property phase diagram for this system has been given to understand the various ferroelectric phenomena. The result could be mainly elucidated by the nanoclusters and the disorder driven nucleation of polar nanoregions contributed by a valence mismatch at one of the cation sites.